Rodinný dům se zubařskou ordinací - Murín, Marek (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Predmetom bakalárskej práce je návrh rodinného domu so zubnou ordináciou. Stavba sa nachádza v obci Sokolnice, v okrese Brno – venkov. Jedná sa o samostatne stojaci, dvojpodlažný a čiastočne podpivničený objekt. Celý objekt je rozdelený na dve časti. Obytná časť je určená k trvalému pobytu štvorčlennej rodiny a prevádzková časť slúži ako zubná ordinácia. Pôdorys domu je obdĺžnikového tvaru s vystupujúcou garážou. Objekt je založený na betónových základových pásoch. Zvislé nosné konštrukcie sú navrhnuté z keramických tvárnic Heluz a betónových tvárnic strateného debnenia. Objekt zastrešuje plochá strecha.

The subject of the bachelor's thesis is the design of a family house with a dental office. The building is located in the village Sokolnice, in the district of Brno-countryside. It is a detached, two story building with a partial basement. The building is divided into two parts. The living area is intended for the permanent residence of a family of four and the other part of the house is designed for a dental office. The floor plan of the house is rectangular with a protruding garage. The building is based on concrete foundation strips. The vertical load-bearing structures are constructed of Heluz ceramic blocks and concrete blocks of lost formwork. The house has a flat roof.
House with dental office
Keywords: rodinný dom; zubná ordinácia; dvojposchodový; čiastočne podpivničený; plochá strecha; family house; dental office; two-storey; partial basement; flat roof